Improvement of islet engrafts by enhanced angiogenesis and microparticle-mediated oxygenation. (May 2016) - Montazeri, Leila; Hojjati-Emami, Shahriar; Bonakdar, Shahin; Tahamtani, Yaser; Hajizadeh-Saffar, Ensiyeh; Noori-Keshtkar, Marjan; Najar-Asl, Mostafa; Ashtiani, Mohammad Kazemi; Baharvand, Hossein
Abstract: A major hindrance in islet transplantation as a feasible therapeutic approach for patients with type 1 diabetes is the insufficient oxygenation of the grafts, which results in cell death in portions of the implant. Here we address this limitation through the application of oxygen-generating microparticles (MP) and a fibrin-conjugated heparin/VEGF collagen scaffold to support cell survival by using a β cell line and pancreatic rat islets. MP are composed of a polyvinylpyrrolidone/hydrogen peroxide (PVP/H2 O2 ) core and poly(d, l -lactide-co-glycolide) (PLGA) shell, along with immobilized catalase on the shell. The presence of MP is sufficient to reduce hypoxia-induced cell dysfunction and death for both cell types, resulting in localization of hypoxia-inducible factor (HIF-1α) into the cytoplasm and enhanced metabolic function. After co-transplantation of MP and a reduced islet mass (250 islet equivalents) within an angiogenic scaffold in the omental pouch of streptozotocin-induced diabetic nude mice, we have observed significantly promoted graft function as evidenced by improved blood glucose levels, body weight, glucose tolerance, serum C-peptide, and graft revascularization. These results suggest that the developed platform has great potential to enhance the efficacy for implants in cases where the cell dosage is critical for efficacy, such as islet transplantation and ischemic tissues.